2021
DOI: 10.1021/acsaelm.1c00679
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite-Based Facile NiO/CH3NH3PbI3 Heterojunction Self-Powered Broadband Photodetector

Abstract: Perovskite light absorbers have drawn attention worldwide for optoelectronic devices due to their solution-processable photovoltaic properties, high carrier mobility, broad spectral range, and integration with a wide range of substrates, etc. A facile NiO/CH3NH3PbI3 heterojunction was fabricated in an ambient environment for self-powered and high-performance photodetector (PD) application. The self-powered PD showed a high responsivity of 33.39 mA/W for UV light and 5.79 mA/W for white light at zero bias, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Although the charge extraction process is hindered by the presence of PbI 2 at the surface of the perovskite, surface modification has become a prime requirement. 33,34 Furthermore, the hole traps resulting from the under-coordinated halide anions on the crystalline surface of MAPbI 3 thin films can induce significant charge accumulation at the perovskite/HTL interface. 35 These trap states existing at the interface can be eliminated by interface engineering to reduce the recombination rate and improve the charge transfer.…”
Section: Role Of Interface and Carrier Transport In Pscsmentioning
confidence: 99%
“…Although the charge extraction process is hindered by the presence of PbI 2 at the surface of the perovskite, surface modification has become a prime requirement. 33,34 Furthermore, the hole traps resulting from the under-coordinated halide anions on the crystalline surface of MAPbI 3 thin films can induce significant charge accumulation at the perovskite/HTL interface. 35 These trap states existing at the interface can be eliminated by interface engineering to reduce the recombination rate and improve the charge transfer.…”
Section: Role Of Interface and Carrier Transport In Pscsmentioning
confidence: 99%
“…However, PRM-modified perovskite thin films preserve the highly crystalline phase. The content of PbI 2 segregated upon air exposure can be calculated from XRD spectra using the following eq : , content of PbI 2 = intensity of PbI 2 intensity of PbI 2 + intensity of MAPbI 3 × 100 It was found that 52.4% PbI 2 was present in the control sample upon air exposure for 20 days.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, PRM-modified perovskite thin films preserve the highly crystalline phase. The content of PbI 2 segregated upon air exposure can be calculated from XRD spectra using the following eq 2: 52,53 content of PbI The standard error of the mean is tabulated. reproducibility of the stability data has been confirmed through carrying the stability test on three sets of PSCs of each control and 2 mg of PRM-containing PSCs.…”
Section: E E Expmentioning
confidence: 99%
“…Among all the available functional materials, metal oxides render various unique properties due to their completely and partially filled ‘s’ and ‘d’ orbitals, respectively. 1 Owing to the unique properties like wide bandgaps, 2 high dielectric constants, 3 and tunable optoelectronic characteristics, 4 the metal oxides are applied in different functional applications, such as solar cells, 5,6 photodetectors, 7,8 supercapacitors, 9 battery electrodes, 10 gas sensors, 11 and electrochromism. 12 Moreover, the metal oxides can be downscaled into nanostructures with different shapes and morphologies, providing an increased surface-to-volume ratio and significantly larger textural boundaries.…”
Section: Introductionmentioning
confidence: 99%